Children's experiences of dental anxiety. Issue 2 (4th July 2016) - Morgan, Annie G.; Rodd, Helen D.; Porritt, Jenny M.; Baker, Sarah R.; Creswell, Cathy; Newton, Tim; Williams, Chris; Marshman, Zoe
Abstract : Background: Dental anxiety is common among children. Although there is a wealth of research investigating childhood dental anxiety, little consideration has been given to the child's perspective. Aim: This qualitative study sought to explore with children their own experiences of dental anxiety using a cognitive behavioural therapy assessment model. Design: Face‐to‐face, semi‐structured interviews were conducted with dentally anxious children aged 11–16 years. The Five Areas model was used to inform the topic guide and analysis. Data were analysed using a framework approach. Results: In total, 13 children were interviewed. Participants described their experiences of dental anxiety across multiple dimensions (situational factors and altered thoughts, feelings, physical symptoms, and behaviours). Participants placed considerable value on communication by dental professionals, with poor communication having a negative influence on dental anxiety and the dentist–patient relationship. Conclusions: This study confirms the Five Areas model as an applicable theoretical model for the assessment of childhood dental anxiety. Children provided insights about their own dental anxiety experiences that have not previously been described.